Treatment and Survival Patterns of Primary Adenosquamous Carcinoma of the Liver: A Retrospective Analysis - Gou, Qiheng; Fu, Shengya; Xie, Yuxin; Zhang, Mengni; Shen, Yali (Frontiers in Oncology, 2021)
Background: Primary adenosquamous carcinoma (ASC) of the liver is an extremely rare tumor. Prognosis of this disease is poor for high aggression. Therefore it is not clear about the early diagnosis, optimal therapy and prognostic factors of the liver ASC. In this study, we retrospectively reviewed a total of 15 patients of primary ASC of the liver within 10 years in our institute. Materials and methods: Fifteen patients with primary ASC of the liver were studied from 2009 to 2018. We collected detailed data of clinicopathological characteristics and analyzed the clinical outcome of these cases. Two of our cases were published in the case report form. Results: All 15 patients have clinical symptoms and met the requirements of pathologic diagnosis. 11/15 patients received surgical resection and three of them received adjuvant chemotherapy. The median survival of the patients who received surgical resection was 7.0 months and the 1-year survival rate was 27%. The median survival of the other 4 non-surgery cases was 3.0 months and they all died within 1 year. For the 3 patients who underwent adjuvant chemotherapy followed surgery, the median survival was 15 months. Univariate analysis revealed that lymph nodes metastasis was associated with poor survival. Conclusion: The Primary ASC of the liver is rather rare with a poor prognosis. It is not easy to diagnose the disease at an early stage. Radical surgery may prolong the survival time of patients. Postoperative adjuvant therapy may bring further extension time to live.